Advanced oxidation processes technology using the Fenton method in Bakung landfill leachate treatment - Teguh, Dedi; Cendekia, Devy; Wulandari, Yeni Ria; Putri, Cynthia Eka; Ramandani, Adityas Agung (Journal of Natural Sciences and Mathematics Research, 2024)
The primary issue at the Bakung final processing location was the high organic and inorganic material concentration. Toxicity, high chemical oxygen demand (COD), a black hue, and an unpleasant smell can usually identify landfill leachate; it can be hazardous if spilled directly into a body of water. Consequently, the implementation of an efficient leachate treatment was necessary. One use of this cutting-edge oxidation process technology consists of the Fenton method for treating leachate. The goals of this study involve implementing the Fenton technique to leachate treatment and ascertaining the impact of reaction time (30, 60, 90, or 120 min) and Fenton molar ratio (1:150, 1:200, or 1:250) on color degradation and chemical oxygen demand (COD). A Fenton molar ratio of 1:150 and a 120-min reaction period were ideal, resulting in maximum color and COD degradation percentages of 91.4% and 92.4%, respectively. The study's findings demonstrate how well the Fenton approach works to reduce COD and color in leachate while also meeting leachate water quality requirements for enterprises and/or ultimate waste processing operations.